Design and Simulation of Timing Recovery Synchronization for Digital Wireless Receiver Based on SDR Technology - Mohammed, Alhamzah Taher (International Journal of Engineering and Technology, 2018)
The design and simulation of the digital wireless receiver with talented time recovery synchronization based on software-defined radio (SDR) technology are present in this paper. The fast growth of wireless communication systems with complexity and constraints increasing is placed upon the hardware to utilize the ability of the developed algorithms. New algorithm efforts were provided for more bandwidth capability to utilize the frequency and time recovery and achieve accurate synchronization between transmitter and receiver. In addition, as high bandwidth receiver become integrated into small mobile, high synchronization is required to attain low power consumption and small size components. This work suggests efficient time recovery techniques to neglect much computation and reduce the power consumption in the digital wireless receiver based on SDR technology. The use of systematic SDR design methodology is to develop the system which provides better synchronization and could reconfigure the equipment without replacement. The proposed design allows to introduce high-level simulation including the constraints and has a functional simulation system capable to translate to hardware implementation without any difficulties. The simulation and implementation results show a promising technique to support the current and future generation of wireless mobile receiver.